PTH-081 Allopurinol Abrogates Thiopurine Induced Liver Injury Without The Need for Metabolite Measurments. (17th August 2016) - Pavlidis, P; Reynolds, R; Ansari, A
Abstract : Introduction: The thiopurines azathioprine and mercaptopurine are widely used as long term immunomodulators in inflammatory bowel diseases (IBD). Reported side effects vary between 10–40% hindering the efficacy and safety of these useful treatments. Hepatotoxicity is one of the commoner side effects (up to 10%) and some investigators have made an association to thiopurine methyltransferase (TMPT) levels as well as hypermethylation. Aim: Report on the use of allopurinol in conjuction to azathioprine (Low Dose Azathioprine Allopurinol- LDAA) in patients who developed thiopurine induced liver injury. Methods: This is a retrospective cohort study. The patients were drawn from a large database of patients at a single District General Hospital by the authors. The outcomes were assessed by review of patient records. Results: We identified 15 (10%) patients who developed thiopurine induced liver injury [median (range) ALT: 74 iu/L (49, 630), ALP: 35 iu/L (20, 120), bilirubin: 8μmol/L (5, 45), time of onset from drug commencement: 12 weeks (6, 30)] in the last 5 years from a prospective cohort of 150 patients who required azathioprine for IBD (Crohn's disease: 8, Ulcerative colitis: 7, 1 with concomitant psoriatic arthropathy and 1 with Takayasu's arteritis). There were 7 (47%) patients with wild type TPMT and 8 (53%) heterozygotes. Seven (78%)of the 9 patients receiving LDAA had a normalisation of aminotransferases after an increase in allopurinol dose from 100 mg to 200 mg while two were eventually diagnosed with primary sclerosing cholangitis. Addition of allopurinol (100 mg) for the 6 patients on azathioprine monotherapy lead to normalisation of aminotransferases. Conclusion: Observations form this data suggest i) Patients who cannot produce high methylated mercaptopurine metabolites (MMP) can develop hepatotoxicity which responds well to allopurinol. ii) Patients may still develop hepatotoxicity on co-therapy with 100 mg of allopurinol, which responds to a dose increase to 200 mg, suggesting an independent hepatocyte protective effect of allopurinol. We have previously suggested a role for reactive oxygen species. iii) Thiopurine metabolites profiles should not be used to guide allopurinol use, as the protective effect is not predicted by high MMP levels. Disclosure of Interest: None Declared